Acute and long-term cardioprotective effects of the Traditional Chinese Medicine MLC901 against myocardial ischemia-reperfusion injury in mice. Issue 1 (December 2017) - Vincent, Anne; Covinhes, Aurélie; Barrère, Christian; Gallot, Laura; Thoumala, Soulit; Piot, Christophe; Heurteaux, Catherine; Lazdunski, Michel; Nargeot, Joël; Barrère-Lemaire, Stéphanie
Abstract MLC901, a traditional Chinese medicine containing a cocktail of active molecules, both reduces cerebral infarction and improves recovery in patients with ischemic stroke. The aim of this study was to evaluate the acute and long-term benefits of MLC901 in ischemic and reperfused mouse hearts.Ex vivo, under physiological conditions, MLC901 did not show any modification in heart rate and contraction amplitude. However, upon an ischemic insult, MLC901 administration during reperfusion, improved coronary flow in perfused hearts.In vivo, MLC901 (4 µg/kg) intravenous injection 5 minutes before reperfusion provided a decrease in both infarct size (49.8%) and apoptosis (49.9%) after 1 hour of reperfusion. Akt and ERK1/2 survival pathways were significantly activated in the myocardium of those mice. In the 4-month clinical follow-up upon an additional continuousper os administration, MLC901 treatment decreased cardiac injury as revealed by a 45%-decrease in cTnI plasmatic concentrations and an improved cardiac performance assessed by echocardiography. A histological analysis revealed a 64%-decreased residual scar fibrosis and a 44%-increased vascular density in the infarct region. This paper demonstrates that MLC901 treatment was able to provide acute and long-term cardioprotective effects in a murine model of myocardial ischemia-reperfusion injuryin vivo .